Exploring the Perceptions of Estonian Teachers' Data Use in School Development - Katrin Rääk; Eve Eisenschmidt; Kairit Tammets (MDPI AG, 2021)
Educational data use practices have a positive impact on evidence-driven school development. Although schools have an abundance of data available to make evidence-driven decisions, it might not be used to its full potential. This paper aimed to explore Estonian teachers' perceptions of data use that support evidence-driven school development. In this qualitative research, semi-structured interviews were conducted with 21 teachers from six different schools. Data were analyzed deductively using a qualitative content analysis. The findings led to two themes, school level and teacher-level factors, that affected the perceptions and practices of data use for evidence. Collaboration was emphasized by both these factors. The results revealed that teachers did not see much interplay between the data they collected and used in their own classrooms for improving teaching and the data used at school-level developments. They evaluated their own data literacy skills as low. Researched schools did not have a systematic approach to data use, and teachers were left without support regarding how to use data and create meaning concerning data school development processes.